Hear My Voice in Silence: Exploring Psychological Well-Being in the Sandwich Generation through Photovoice - Nur, Nurul Kamilah Bennu; Pranungsari, Dessy; Zulchairani, Asviannisa Rachma; Alifia, Kayla Naifah; Wulaningrum, Dita Sari (Universitas Ahmad Dahlan, 2024)
This research contributes to understanding adolescents' awareness of psychological wellbeing within the sandwich generation. The unique challenges faced by sandwich generation teenagers, due to the demands of balancing multiple responsibilities, heighten their vulnerability to mental health issues and suicidal ideation. The study involved eight participants who met specific criteria: active college students in Yogyakarta, aged 18 to 22, residing in Yogyakarta, employed in part-time, full-time, or freelance work, who had experienced thoughts of self-harm, and who were willing to participate. A qualitative approach was employed using the photovoice method, guided by the SHOWED framework (focusing on what is Seen, what is Happening, how it relates to Our lives, why it Exists, and what can be Done about it). Data analysis was conducted through content and thematic analysis, using both photographs and narratives as primary data sources. The study provides a comprehensive understanding of the psychological well-being of the sandwich generation, exploring dimensions such as perspective, environmental mastery, mood, life purpose, selfacceptance, autonomy, personal growth, and religiosity.